Gene Expression Signatures of Lymph Node Metastasis in Oral Cancer: Molecular Characteristics and Clinical Significances - Liu, Xiqiang (2010)
Even though lymph node metastasis accounts for the vast majority of cancer death in patients with oral cancer (OC), the molecular mechanisms of lymph node metastasis remain elusive. Genome-wide microarray analyses and functional studies in vitro and in vivo, along with detailed clinical observations, have identified a number of molecules that may contribute to lymph node metastasis. These include lymphangionenic cytokines, cell adhesion molecules, basement membrane-interacting molecules, matrix enzymes and relevant downstream signaling pathways. However, defined gene signatures from different studies are highly variable, which hinders their translation to clinically relevant applications. To date, none of the identified signatures or molecular biomarkers has been successfully implemented as a diagnostic or prognostic tool applicable to routine clinical practice. In this review, we will first introduce the significance of lymph node metastasis in OC, and clinical/experimental evidences that support the underlying molecular mechanisms. We will then provide a comprehensive review and integrative analysis of the existing gene expression studies that aim to identify the metastasis-related signatures in OC. Finally, the remaining challenges will be discussed and our insights on future directions will be provided.